PENGARUH SERBUK BATU PARAS BELAYU SEBAGAI SUBSTITUSI SEMEN TERHADAP KUAT TEKAN BETON - Suhartapa, I Made Ari; Widnyana, I Nyoman Suta; Laintarawan, I Putu (Widya Teknik, 2024)
Cement is the most important building material in making concrete, cement is formed from the oxidation process or heating of limestone using coal at high temperatures. The heating process produces excess CO? which has a negative impact on the environment. So in this research, the researchers conducted research on the effect of sandstone powder (SBP) as a substitute for Portland cement (SPI) in concrete mixtures because sandstone contains silica and alumina minerals which are suitable for use. as pozzolan. The test object used in this study was a cube measuring (150 x 150 x 150) mm, with the ratio: (0% SBP: 100 SPI), (2.5% SBP: 97.5% SPI), (5%SBP: 95% SPI) and (10% SBP: 90% SPI) which were tested at 28 days of age. Concrete mix planning (mix design) is carried out based on SNI 7656-2012 with concrete design quality 20.75 MPa, classified as concrete quality for building structures. From the test results, it was found that the effect of sandstone powder as a cement substitute in the concrete mixture increased the compressive strength of the concrete at a percentage of 2.5% -5%, and at a percentage of 10% the compressive strength of the concrete decreased.